Factors influencing the effectiveness of training programme in Shapadu Security Sdn Bhd / Muhammad Uqbah Zainal Abidin and Nur Alees Ali - Zainal Abidin, Muhammad Uqbah; Ali, Nur Alees (Faculty of Business and Management, 2013)
The purpose of this research paper is to get a better understanding on what factors can give influence to the effectiveness of training programme in Shapadu Security Sdn Bhd. Three main aspects that usually a company will take into consideration are training module, training environment and the trainers’ ability. These factors will help to evaluate whether the training programme achieve its effectiveness or vice versa. Based on the study constructed, it showed that there is a positive and significant relationship between factors that influence training programme which are training module, training environment and trainers’ ability with its effectiveness. Apart from that, from the test that have been constructed, it showed high result on paired T-test which most of the respondents (trainee) claimed that the training programme provided by Shapadu Security Sdn Bhd give impacts to their daily works by improve their skills and knowledge.